Investigation of Realistic Fire Scenarios Involving Cryogenic Storage Tanks - Robert Eberwein; Jennifer Heßmann; Jan Werner; Giordano Emrys Scarponi; Valerio Cozzani; Frank Otremba (Chemical Engineering Transactions, 2025)
The number of vehicles using or transporting cryogenic fuels such as Liquefied Hydrogen (LH2) or Liquefied Natural Gas (LNG) increases fast in the land transportation sector. Does this also entail new risks for instance from a BLEVE? A key to answer this question is to research representative fires by its characterization and its effect on the insulation. At BAM’s technical test side in Germany, a test series was started to answer this question among others. This paper presents results on a pool fire under a colorimeter, that simulates a tank. The investigation points out, that the full fire characterization approach allows to represent the fire. The findings are relevant for the investigation of a representative design fire that is applicable for the approval and improvement of tanks as well as to research accident scenarios and their consequences.